Role of periodontal ligament fibroblasts in periodontitis: pathological mechanisms and therapeutic potential - Yijie Huang; Ying Tang; Ruiqi Zhang; Xiao Wu; Li Yan; Xiling Chen; Qianqi Wu; Yiyan Chen; Yingtao Lv; Yuan Su (Journal of Translational Medicine)
Abstract Periodontal ligament fibroblasts (PDLFs) play a crucial role in the etiology of periodontitis and periodontal tissue regeneration. In healthy periodontal tissues, PDLFs maintain the homeostasis of periodontal soft and hard tissues as well as the local immune microenvironment. PDLFs also have the potential for multidirectional transdifferentiation and are involved in periodontal tissue regeneration. On the other hand, PDLFs can become dysfunctional and acquire an inflammatory phenotype to secret various inflammatory cytokines when affected by pathological factors. These cytokines further trigger immune and inflammatory events, and lead to destruction of periodontal soft and hard tissues as well as damage to the regenerative potential of PDLFs. This review summarizes the physiological functions of PDLFs. Meanwhile, this review also highlights recent insights into the pathological mechanisms driving the development of periodontitis through dysfunctional PDLFs and the negative impact on periodontal tissue regeneration. Additionally, this paper summarizes strategies for targeting PDLFs to treat periodontitis, involving blocking multiple stages of the inflammatory response induced by PDLFs and promoting the multidirectional transdifferentiation of PDLFs. Future research directions are proposed to address important questions that have not yet been answered in this field. This article provides a reference for understanding the important role of PDLFs in the pathological mechanisms of periodontitis and for developing new strategies for targeting PDLFs in periodontitis treatment. Graphical Abstract